A Cox parametric bootstrap test of the von Liebig hypotheses - Kaitibie, S.; Nganje, W.E.; Brorsen, B.W.; Epplin, F.M. (Wiley, 2007)
This study uses a Cox parametric bootstrap test to select between two specifications of the von Liebig hypothesis, a switching regression (SR) model, and a linear response function with a stochastic plateau. Specifying the production function as a linear response function with a stochastic plateau yields a superior approximation of the data for livestock gain as a function of forage allowance than the SR approach.